2022
DOI: 10.1038/s41598-022-11846-w
|View full text |Cite
|
Sign up to set email alerts
|

Copper(II) invigorated EHU-30 for continuous electroreduction of CO2 into value-added chemicals

Abstract: The doping of zirconium based EHU-30 and EHU-30-NH2 metal–organic frameworks with copper(II) yielded a homogeneous distribution of the dopant with a copper/zirconium ratio of 0.04–0.05. The doping mechanism is analysed by chemical analysis, microstructural analysis and pair distribution function (PDF) analysis of synchrotron total scattering data in order to get deeper insight into the local structure. According to these data, the Cu(II) atoms are assembled within the secondary building unit by a transmetalati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 22 publications
1
18
0
2
Order By: Relevance
“…They normally used bipolar membranes that could generate large amounts of CO 2 in situ. We can also highlight many works by A. Irabien et al [ 28 , 29 , 30 , 31 , 32 , 33 ] centered on the electroreduction of CO 2 towards high added value products such as methane, methanol, formic acid, ethylene, etc. These works focused on catalysts derived from copper and nickel to enhance the selectivity and efficiency of the CO 2 ER.…”
Section: Introductionmentioning
confidence: 77%
“…They normally used bipolar membranes that could generate large amounts of CO 2 in situ. We can also highlight many works by A. Irabien et al [ 28 , 29 , 30 , 31 , 32 , 33 ] centered on the electroreduction of CO 2 towards high added value products such as methane, methanol, formic acid, ethylene, etc. These works focused on catalysts derived from copper and nickel to enhance the selectivity and efficiency of the CO 2 ER.…”
Section: Introductionmentioning
confidence: 77%
“…The thermogravimetric (TG) curve showed that it can be stable up to 379 °C (Figure S6). Atomic force microscopy (AFM) images showed that the bulk samples were transformed into nanosheet samples with different thicknesses of 55, 11.2, 2.2, and 1.1 nm, respectively, after being treated by rod ultrasonication for different times (12,14,16, and 18 h) (Figures 1e, 1f and S7− S11). However, when the rod stripping time is greater than 24 h, the material breaks down into very small fragments (Figure S8), which is due to the destruction of intralayer supramolecular interactions in the MOL.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…gives them the upper hand over conventional porous materials like silica, zeolites, and porous carbon. MOFs not only provide a platform to achieve NPs of desirable sizes and fine dispersion, which will effectively reduce the catalyst cost, but also offer paths for the transfer of the substrates and/or products in their pores and increase the mass activity. , Several MOF-based electrocatalysts, including pristine MOFs and their derivatives, are reported in the literature for electrocatalytic CO 2 reduction. Introduction of metal nanoparticles with precise size on the exact location of MOFs is important for understanding the active site of the catalyst. This will shed light on the structure–property correlation.…”
Section: Introductionmentioning
confidence: 99%